3-(2-furyl)-4-(4-methoxyphenyl)-1H-1,2,4-triazole-5(4H)-thione - Yildirim, SÖ; Akkurt, M; Koparir, M; Cansiz, A; Sekerci, M; Heinemann, FW (Int Union Crystallography, 2004)
The title compound, C13H11N3O2S, has a non-planar conformation. The dihedral angles are 3.41 ( 8) and 85.48 ( 7) degrees between the triazole ring plane and the furan and benzene ring planes, respectively. The crystal packing is stabilized by several hydrogen bonds.